2004
DOI: 10.1093/ps/83.6.990
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Copper Source on Phosphorus Retention in Broiler Chicks and Laying Hens

Abstract: Copper sulfate is often added to broiler and laying hen diets at prophylactic dosages due to its antimicrobial and growth promoting effects despite reduced P digestibility, whereas P use from other Cu sources is unknown. Therefore, male broiler chicks were fed diets containing 0 or 250 ppm Cu from Cu sulfate (Cu SUL), Cu citrate (Cu CIT), Cu lysinate (Cu LYS), or CuCl from 9 to 22 d of age (8 cages/diet, 6 birds/cage) to determine the effect of each Cu source on performance characteristics, bone mineralization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 13 publications
4
23
2
Order By: Relevance
“…In contrast to the result of present study, other researchers reported that Cu supplemented at the excess levels of the requirements of broilers (8 mg/kg) recommended by NRC (1994) did not have significant effects on growth performance (Banks et al, 2004;Pang and Applegate, 2007). This is because the extent of the microbial challenge may influence the response of broilers to dietary Cu supplementation (Karimi et al, 2011).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to the result of present study, other researchers reported that Cu supplemented at the excess levels of the requirements of broilers (8 mg/kg) recommended by NRC (1994) did not have significant effects on growth performance (Banks et al, 2004;Pang and Applegate, 2007). This is because the extent of the microbial challenge may influence the response of broilers to dietary Cu supplementation (Karimi et al, 2011).…”
Section: Discussioncontrasting
confidence: 99%
“…Phytin has chemical characteristics enabling it to bind to Zn and other minerals within the digesta of the small intestine and render the minerals less available for absorption (Banks et al, 2004). Furthermore, Persson et al (1998) found that the minerals Cu and Zn have highest affinity for phytic acid.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, tibia Cu concentration was found an increasing trend (P<0.1) in 56-dayand 126-day-old turkeys fed a Cu-AA chelate supplemented diet, compared to birds given a diet with Cu-sulphate. In an experiment performed by Banks et al (2004b), bone mineralization results indicated that chickens fed diet with Culysinate had the greatest (P≤0.05) tibia and toe ash percentages and weights as compared with birds fed Cu-citrate or Cu-sulphate diets. Our results show that the tibia major mineral concentration (Ca and P) were unaffected (P>0.1) by dietary treatments both at days 56 and 126 of the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…To the author's knowledge, there are very few studies investigating the effects of organic copper compounds in laying hens. Controversies exist in these studies concerning the levels of organic copper complexes recommended for laying hens without having deleterious effects on performance and metabolism [17,22,23]. Determination of possible changes due to copper proteinate, which is one of the organic copper compounds at high levels, in performance and metabolism as well as its accumulation in the liver and residue in the egg yolk may be of importance for health concern in both animals and humans.…”
Section: Discussionmentioning
confidence: 99%
“…Chelated products or proteinates have superior bioavailability over inorganic copper sources [14][15][16]. The purpose of a chelated product is to protect the compound of interest from digestion or complex formation thereby enabling the protected compound to reach its target site [17]; thus, lower dietary inclusion levels are required due to the better absorption [16], which enhances the efficiency. Although, animals vary by species in their sensitivity, poultry can tolerate many times their usual daily intakes of copper [1,2].…”
Section: Introductionmentioning
confidence: 99%